The Supreme Federal Court as Queen of Chess: Partisan Fragmentation and Judicial Empowerment in Brazil - Barbosa, Leon Victor de Queiroz; Carvalho, Ernani (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: This article deals with the Supreme Federal Court’s empowerment trajectory, exploring exogenous variables in order to explain what made the Supreme Court so institutionally powerful, and how it happened. After the classic studies on the global expansion of the judicial power, that pointed to a myriad of causes as a result of the phenomenon, several recent researches have indicated the political-party fragmentation as the main cause of judicial empowerment. Seeking to corroborate these analyses, the present work analyzes the institutional empowerment of the Brazilian Judiciary from 1945 to 2015, testing the hypothesis the greater the party fragmentation, more institutional power the STF holds. Materials and Methods: As a dependent variable, a synthetic indicator was created to measure the institutional power of the Federal Supreme Court year by year. The independent variables measure the party composition of the Chamber of Deputies annually for the same period. In addition to these variables, other measures were imported from the V-Dem database. For this analysis, simple linear, generalized linear and multinomial models were used. Results: We identified significant impact of party fragmentation on institutional empowerment of the Supreme Court. In all tests, party fragmentation increased the chances of institutional empowerment of the Brazilian judiciary. Discussion: The exogenous reforms that generated this empowerment took place with the support of the Executive and the leniency of the Legislative, transforming the Brazilian Supreme Court into the Queen of the Chess. KEYWORDS: Judiciary Power; Partisan Fragmentation; judicial empowerment; Supreme Federal Court; multinomial; factorial analysis.